A Fort at Skitten, Wick, Caithness, with Notes on Flint Implements from the same County - Duff-Dunbar, Louisa (Proceedings of the Society of Antiquaries of Scotland, 1935)
This paper examines the artefacts found at the hillfort at Skitten, Kilminster, in the parish of Wick, Caithness. There are at least three sites, two within the rampart and one to the southside. Among the finds were three hearths, three fragments of flint, a Bronze Age cinerary urn, a claystone polisher, and one tiny bit of burnt bone. Notably, there was no trace of a cairn. Duff-Dunbar argues Skitten was a flint workers site, decidedly a poor one, due to the large quantity of small round scrapers and lack of fine finished implements. The paper concludes by comparing Skitten with flints sites elsewhere in Caithness, Moray, Aberdeen, and Banff.